2018
DOI: 10.1016/j.stemcr.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

DSG2 Is a Functional Cell Surface Marker for Identification and Isolation of Human Pluripotent Stem Cells

Abstract: SummaryPluripotent stem cells (PSCs) represent the most promising clinical source for regenerative medicine. However, given the cellular heterogeneity within cultivation and safety concerns, the development of specific and efficient tools to isolate a pure population and eliminate all residual undifferentiated PSCs from differentiated derivatives is a prerequisite for clinical applications. In this study, we raised a monoclonal antibody and identified its target antigen as desmoglein-2 (DSG2). DSG2 co-localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…S6), suggesting that DSG2 may contribute to CTC survival during circulation and may help maintain cancer stemness. Consistent with this notion, DSG2 has recently been identified as a marker for pluripotent stem cells (PSCs) and is critical for PSC self-renewal and reprogramming (37). These observations could partially explain why there was no significant difference or even higher single CTC numbers in mice bearing cancer cells with high overall DSG2 level (shCtrl) compared to mice bearing DSG2-depleted (shDSG2) cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…S6), suggesting that DSG2 may contribute to CTC survival during circulation and may help maintain cancer stemness. Consistent with this notion, DSG2 has recently been identified as a marker for pluripotent stem cells (PSCs) and is critical for PSC self-renewal and reprogramming (37). These observations could partially explain why there was no significant difference or even higher single CTC numbers in mice bearing cancer cells with high overall DSG2 level (shCtrl) compared to mice bearing DSG2-depleted (shDSG2) cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, CTCs that can survive in the circulatory system and colonize in distant organs are thought to be cancer stem-like cells and are highly correlated with metastasis (47,48). Consistent with this notion, DSG2 has recently been identified as a marker for pluripotent stem cells (PSCs) and is critical for PSC self-renewal and reprogramming (49). How DSG2 may contribute to cancer stemness is another topic of interest for further experiments.…”
Section: Discussionmentioning
confidence: 86%
“…In epithelial cells, adenovirus binding to DSG2 triggers events reminiscent of epithelial-to-mesenchymal transition, leading to transient opening of intercellular junctions [ 158 ]. DSG2 also regulates β-catenin-mediated EMT signaling in pluripotent stem cells [ 159 ].…”
Section: Appendixmentioning
confidence: 99%
“…They also identified two other mAbs that bind to surface proteins on both hESCs and cancer cell lines, though the identities of the antigens were not determined [27]. Independently, Son et al, using conventional hybridoma technology, raised a panel of mAbs against hESC, of which two mAbs were shortlisted and characterized [28,29]. The first mAb, 4-63, was found to bind to the antigen L1 cell adhesion molecule (L1CAM) on undifferentiated PSCs [28].…”
Section: Mabs For Regenerative Cell Therapymentioning
confidence: 99%
“…L1CAM was found to play an important role in self-renewal by activating fibroblast growth factor receptor 1 signaling. The second mAb binds to desmoglein-2 (DSG2) on undifferentiated hESCs, and its surface expression is rapidly downregulated upon differentiation [29]. Their studies further revealed that DSG2 is essential to the self-renewal of PSCs and the acquisition of pluripotency during somatic cell reprogramming by controlling β-catenin/slug-mediated epithelial mesenchymal transition.…”
Section: Mabs For Regenerative Cell Therapymentioning
confidence: 99%